ANALISIS FAKTOR PENGGUNAAN LAYANAN GO-PAY OLEH GENERASI MILLENIAL DI KOTA DENPASAR - Gusi Putu Lestara Permana; Ni Luh Putu Puspita Dewi (Jurnal Widya Akuntansi dan Keuangan, 2020)
The aim of this study was determine factors that encourage millenials using GO-PAY services. In this study using three independent variables, self-efficacy, government regulation and word of mouth, with one dependent variable, the use of services. Data collection techniques in this study used a questionnaire. The sample in this study were 70 respondents, namely in millennials who use gopay services in Denpasar area with the purposive sampling method. Data were analyzed using multiple linear regression analysis techniques, coefficient of determination, simultaneous significance test (F test), and partial test (t test) and running in Statistical Package for the Social Sciences (SPSS) software for windows. The results of this study found that 1) Self-efficacy had a positive and significant effect on the use of gopay services in millennials in Denpasar. 2) Government Regulation has a positive and significant effect on the use of gopay services in millennial generation in Denpasar City. 3) Word of mouth has a positive and significant effect on the use of gopay services in millennials in Denpasar.